Tratamento de efluente de lavanderia têxtil utilizando plasma - Santos, Thiago Damião dos (2018)
The textile industry generates high volumes of liquid effluents, which have as characteristic the heterogeneity of its composition, due to compounds like salts, acids, alkalis, sequestrants, dispersants, reducing agents and oxidants etc. Besides having high staining, due to the presence of dyes. In this context, the present work investigated the applicability of the advanced oxidative process using plasma to promote the electrolysis of effluent from textile laundry. It has been found that the process is effective in removing color from the effluent in two hours of processing, with results exceeding 80% removal. There was also a reduction in the values of turbidity, COD and smell removal. The results of the phytotoxicity tests using lettuce seeds (Lactuca Sativa) show that 100% germination of the seeds were used using the treated effluent and that the roots of these seeds are larger than those cultivated with distilled water, proving the decontamination of the effluent and suggesting the presence of nutrients.